A Transannular Polyene Tetracyclization for Rapid Construction of the Pimarane Framework. Issue 30 (1st April 2020) - Feilner, Julian M.; Wurst, Klaus; Magauer, Thomas
Abstract: Polyene cyclizations are one of the most powerful and fascinating chemical transformations to rapidly generate molecular complexity. However, cyclizations employing heteroatom‐substituted polyenes are rare. Described here is the tetracyclization of a dual nucleophilic aryl enol ether involving an unprecedented transannular endo ‐termination step. In this transformation, five stereocenters, two of which are quaternary, four carbon–carbon bonds, and four six‐membered rings are formed from a readily available cyclization precursor. The realization of this cyclization enabled short synthetic access to the tricyclic diterpenoid pimara‐15‐en‐3α‐8α‐diol. Abstract : The tricyclic natural product pimara‐15‐en‐3 α ‐8 α ‐diol comprises three quaternary carbon centers and six stereocenters, four of which are adjacent. S yn ‐pentane interactions of all four axial substituents generate considerable strain in the molecule. Reported here is a 13 step synthesis that features a powerful polyene tetracyclization involving an unprecedented transannular endo ‐termination step.